Alternative Methods of Vaccine Delivery: An Overview of Edible and Intradermal Vaccines - E. Criscuolo; V. Caputo; R. A. Diotti; G. A. Sautto; G. A. Kirchenbaum; N. Clementi (Journal of Immunology Research)
Vaccines are recognized worldwide as one of the most important tools for combating infectious diseases. Despite the tremendous value conferred by currently available vaccines toward public health, the implementation of additional vaccine platforms is also of key importance. In fact, currently available vaccines possess shortcomings, such as inefficient triggering of a cell-mediated immune response and the lack of protective mucosal immunity. In this regard, recent work has been focused on vaccine delivery systems, as an alternative to injectable vaccines, to increase antigen stability and improve overall immunogenicity. In particular, novel strategies based on edible or intradermal vaccine formulations have been demonstrated to trigger both a systemic and mucosal immune response. These novel vaccination delivery systems offer several advantages over the injectable preparations including self-administration, reduced cost, stability, and elimination of a cold chain. In this review, the latest findings and accomplishments regarding edible and intradermal vaccines are described in the context of the system used for immunogen expression, their molecular features and capacity to induce a protective systemic and mucosal response.